Advances in Micro/Nanoporous Membranes for Biomedical Engineering. Issue 7 (29th January 2021) - Sun, Meilin; Han, Kai; Hu, Rui; Liu, Dan; Fu, Wenzhu; Liu, Wenming
Abstract: Porous membrane materials at the micro/nanoscale have exhibited practical and potential value for extensive biological and medical applications associated with filtration and isolation, cell separation and sorting, micro‐arrangement, in‐vitro tissue reconstruction, high‐throughput manipulation and analysis, and real‐time sensing. Herein, an overview of technological development of micro/nanoporous membranes (M/N‐PMs) is provided. Various membrane types and the progress documented in membrane fabrication techniques, including the electrochemical‐etching, laser‐based technology, microcontact printing, electron beam lithography, imprinting, capillary force lithography, spin coating, and microfluidic molding are described. Their key features, achievements, and limitations associated with micro/nanoporous membrane (M/N‐PM) preparation are discussed. The recently popularized applications of M/N‐PMs in biomedical engineering involving the separation of cells and biomolecules, bioparticle operations, biomimicking, micropatterning, bioassay, and biosensing are explored too. Finally, the challenges that need to be overcome for M/N‐PM fabrication and future applications are highlighted. Abstract : Micro/nanoporous membranes (M/N‐PMs) present quite practical and potential value for extensive biological and medical applications involving separation, patterning, tissue reconstruction, high‐throughput manipulation/analysis, and biosensing. In this work, the recent advances in fundamentals of M/N‐PMs, as well as their applications in biomedical engineering are systematically summarized, providing insights into membrane design, microdevice establishment, and further performance.